Forecasting of wheat production in Bangladesh (Bangladesh Journal of Agricultural Research, 2010)
The present study was undertaken to find out appropriate model using seven contemporary model selection criteria that could best describe the growth pattern of wheat production in Bangladesh and its three major areas like Dmajpur, Rajshahi, and Rangpur districts during the time periods 1971-72 to 2004-05. It appeared from the study that the best fitted model for wheat production in Bangladesh, Dinajpur, Rajshahi, and Rangpur were quadratic, linear, and cubic model. It means that the assumption of constant annual rate of growth in percent that lies behind the use of exponential/compound model which is very common in describing growth pattern was not true for the growth pattern of wheat production in Bangladesh. In Dinajpur District, linear model seemed to be appropriate. Five-years’ forecasts of wheat production in Bangladesh, Dinajpur, Rajshahi, and Rangpur districts in the year 2005/06 were 1.55, 0.31, 0.24, and 0.37 million tons, respectively, with a 95 percent confidence interval. The analysis found that if the present growth rates continue then the wheat production in Bangladesh, and Dinajpur, Rajshahi, and Rangpur districts would be 1.54, 0.35, 0.31, and 0.59 million tons, respectively, in the year 2009/10. Keywords: Forecasting; wheat production in Bangladesh. DOI: 10.3329/bjar.v35i1.5863Bangladesh J. Agril. Res. 35(1) : 17-28, March 2010